2007
DOI: 10.1149/1.2789294
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Deposition of Ruthenium from an Amidinate Precursor

Abstract: Atomic layer deposition ͑ALD͒ and pulsed chemical vapor deposition ͑CVD͒ were used to make ruthenium ͑Ru͒ thin films from a volatile Ru amidinate precursor, bis͑N,NЈ-di-tert-butylacetamidinato͒ruthenium͑II͒ dicarbonyl. The CVD films were grown without any coreactant, while the ALD films used ammonia as a coreactant. The films are fine-grained polycrystalline ruthenium with high purity ͑Ͻ0.2% impurities͒. Ru grew as a continuous, electrically conductive, pinhole-free film on tungsten nitride ͑WN͒ films even for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 22 publications
(15 reference statements)
3
49
0
Order By: Relevance
“…The ruthenium amidinate precursor, bis(N,N'-di-tert-butylacetamidinato)ruthenium(II) dicarbonyl, has been synthesized in our group and used to deposit ruthenium thin films with or without NH 3 as co-reactant. [7,8] Highly pure and conductive films have been conformally deposited in holes with aspect ratio 40:1. [8] In this research, we report an ALD process for ruthenium thin films using this amidinate precursor and O 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ruthenium amidinate precursor, bis(N,N'-di-tert-butylacetamidinato)ruthenium(II) dicarbonyl, has been synthesized in our group and used to deposit ruthenium thin films with or without NH 3 as co-reactant. [7,8] Highly pure and conductive films have been conformally deposited in holes with aspect ratio 40:1. [8] In this research, we report an ALD process for ruthenium thin films using this amidinate precursor and O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Highly pure and conductive films have been conformally deposited in holes with aspect ratio 40:1. [8] In this research, we report an ALD process for ruthenium thin films using this amidinate precursor and O 2 . We found that the growth mechanism is quite different from the process using NH 3 as a co-reactant.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Some transition metals, such as Cu, Co, Fe, Ru, Mn, and Ni, as well as their nitrides and oxides and rare earth oxides have been successfully grown by ALD from the corresponding amidinate precursors. 7,[11][12][13][14][15][16] However, the surface chemistry of these relatively new precursors has not yet been investigated in situ, because most studies to-date have focused on ex situ film characterization by electrical, physical, or chemical measurements.…”
Section: Introductionmentioning
confidence: 99%
“…2.286(2) W(1)-C (12) 1.964(2) W(1)-C(13) 1.940(2) W(1)-C (14) 2.292(2) W(1)-C (15) 2.202(3) W(1)-C (16) 2.326(2) N(1)-W(1)-N(2) 37.12 ( 148.65 (14) characterized molybdenum(II) and tungsten(II) complexes containing the fac-M(allyl)(CO) 2 fragment [1][2][3][4][5]. The structural features of the the fac-M(allyl)(CO) 2 moieties are very similar in 1a, 2b, 3a, and 4b.…”
Section: Tablementioning
confidence: 99%